A comparative study of the effects of aqueous mixed amines on biogas upgrading based on 13C nuclear magnetic resonance (NMR) analysis. (1st October 2022) - Meng, Fanzhi; Han, Siyu; Meng, Yuan; Ju, Tongyao; Lin, Li; Jiang, Jianguo
Abstract: As a key technology for biogas upgrading, mixed amines scrubbing can meet the world's demand for renewable energy by ensuring high methane (CH4 ) purity while achieving low energy regeneration. In this paper, several monoamines with excellent performance in biogas upgrading process were selected to study the effectiveness of their blends for biogas upgrading and compared with 30 wt% monoethanolamine (MEA). The biogas upgrading effect, carbon dioxide (CO2 ) loading, regeneration effect and CO2 desorption heat of mixed amines were determined by batch experiments. 13 C NMR was used to mechanistically interpret and quantify the carbocation trend of the amine solution before and after the reaction and regeneration. The results showed that the biogas upgrading and regeneration effect of the mixed amines combined with methyl monoethanolamine (MMEA) and N-methyldiethanolamine (MDEA) was the best, and its initial methane purity, saturated CO2 loading, regeneration rate and CO2 desorption heat after upgrading were 100%, 0.617 mol CO2 /mol amine, 54.3% and 64.91 kJ/mol CO2, respectively. Except for the saturated loading which was second only to MMEA/dimethyl monoethanolamine (DMMEA) with 0.624 mol CO2 /mol amine, all the performances are optimal and the CO2 desorption heat is 19.01% lower than that of 30 wt% MEA, which can effectively reduce the regeneration energy consumption of the reaction. The results of 13 C NMR showed that the increase of bicarbonate content could effectively reduce the regeneration energy consumption and enhance the initial regeneration rate, and the increase of carbamate could accelerate the initial uptake rate and methane purity, which could provide theoretical support for the subsequent screening of mixed amines to achieve different reaction purposes. Graphical abstract: Image 1 Highlights: MMEA/MDEA = 3/1 can achieve 100% CH4 purity and 0.617 mol CO2 /mol amine CO2 uptake. MMEA/MDEA = 3/1 regeneration energy consumption is 19.01% lower than 30 wt% MEA. All mixed amines have high CO2 /CH4 selectivity. The rapid production of carbamate facilitates the initial absorption rate. The production of bicarbonate facilitates the initial regeneration rate.